2019
DOI: 10.31883/pjfns-2019-0001
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Quality of Edible Marine Bivalves from the Southern Coast of Italy, Mediterranean Sea

Abstract: for the synthesis of resolvins, which are believed to play a key role in terminating inflammatory processes [Kohli & Levy, 2009]; moreover, they have benefi cial effects on other diseases, namely skin disease, asthma, arthritis, nephritis, lupus erythematous, multiple sclerosis, and certain types of cancers [Harris, 2010; Massaro et al., 2010]. PUFAs are infl uenced by taxonomic relations and environmental conditions and depend on species, nutrient habits, food availability and physiological conditions, so the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
22
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 51 publications
(51 reference statements)
14
22
2
2
Order By: Relevance
“…The raw mussel M. galloprovincialis is a good source of n-3 PUFA with low content of n-6 PUFA, as reported in previous studies [5,9,23,24]. The data of this study showed that the level of n-3 PUFA was always higher than the level of n-6 for all types of cooking, except for fried sample (Tables 1-3).…”
Section: Fatty Acids Profilesupporting
confidence: 81%
“…The raw mussel M. galloprovincialis is a good source of n-3 PUFA with low content of n-6 PUFA, as reported in previous studies [5,9,23,24]. The data of this study showed that the level of n-3 PUFA was always higher than the level of n-6 for all types of cooking, except for fried sample (Tables 1-3).…”
Section: Fatty Acids Profilesupporting
confidence: 81%
“…It is worth noting that although there are many reports showing that bivalves are rich in n‐3 PUFA, especially EPA and DHA (Manthey‐Karl et al, ; Passi et al, ; Ricardo et al, ), but there was no report on the FA composition can be improved by hybridization. Compared with other studies (Table ), all progenies in the present study had much higher total lipid content (9.1%–9.5% wet weight) than wild and farmed oysters (1.2%–6.7% wet weight) collected from Mediterranean sea (Biandolino et al, ), Beihai, China (Qin et al, ), Rushan Bay, China (Zhu et al, ), Kerala, India (Asha, Anandan, Mathew, & Lakshmanan, ), Malaysia (Aziz, Azlan, Ismail, Alinafiah, & Razman, ), Canada (Pernet, Gauthier‐Clec, & Mayrand, ), Jiaozhou Bay, China (Xu & Yang, ), and Bizerte lagoon, north of Tunisia (Dridi, Salah Romdhane, & Elcafsi, ). The EPA compositions (12.7%–14.9%) of all progenies were comparable to other oyster (EPA = 7.5%–13.3%) (Aziz et al, ; Biandolino et al, ; Dridi et al, ; Pernet et al, ; Qin et al, ; Xu & Yang, ; Zhu et al, ), except for farmed C. madrasensis in Kerala, India (Asha et al, ).…”
Section: Discussioncontrasting
confidence: 64%
“…Compared with other studies (Table ), all progenies in the present study had much higher total lipid content (9.1%–9.5% wet weight) than wild and farmed oysters (1.2%–6.7% wet weight) collected from Mediterranean sea (Biandolino et al, ), Beihai, China (Qin et al, ), Rushan Bay, China (Zhu et al, ), Kerala, India (Asha, Anandan, Mathew, & Lakshmanan, ), Malaysia (Aziz, Azlan, Ismail, Alinafiah, & Razman, ), Canada (Pernet, Gauthier‐Clec, & Mayrand, ), Jiaozhou Bay, China (Xu & Yang, ), and Bizerte lagoon, north of Tunisia (Dridi, Salah Romdhane, & Elcafsi, ). The EPA compositions (12.7%–14.9%) of all progenies were comparable to other oyster (EPA = 7.5%–13.3%) (Aziz et al, ; Biandolino et al, ; Dridi et al, ; Pernet et al, ; Qin et al, ; Xu & Yang, ; Zhu et al, ), except for farmed C. madrasensis in Kerala, India (Asha et al, ). For the DHA composition, the DHA composition of all progenies in present study was higher (7.0%–11.2%) than that of Wild M. galloprovincialis (5.3 ± 0.2%) and Wild C. gigas (6.4 ± 0.4%) in Jiaozhou Bay, China (Xu & Yang, ), but was comparable or lower than oysters in other reports (Asha et al, ; Biandolino et al, ; Dridi et al, ; Pernet et al, ; Qin et al, ; Zhu et al, ).…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Same as Asian hard clam M. lusoria [18], Palmitoleic acid (C16:1n7, 8.16±0.11 %) and Cis-9-octadecenoic acid (C18:1n9c, 7.45±0.06 %) were also the major MUFAs in clams C. erycina. But in the bivalves Arca noae and F. glaber [40], Cis-9-hexadecenoic acid (C16:1) and C18:1n9c are the major MUFAs. Among PUFAs, Cis-4,7,10,13,16, 19-docosahexaenoic acid (C22:6n3, DHA, 13.55±0.55 %), Cis-5, 8, 11, 14, 17-eicosapentaenoic acid (C20:5n3, EPA, 7.58±0.19 %) and Cis-5, 8, 11, 14-eicosatetraenoic acid (C20:4n6, 6.25±0.23 %) were dominant in clams C. erycina, which was similar to the results found in Crassostrea gigas, but different from the results in Limaria tuberculate and Mimachlamys varia [40].…”
Section: Fatty Acidsmentioning
confidence: 99%